Change in the psychological self in people living with dementia: A scoping review. (April 2023) - Mentzou, Aikaterini; Sixsmith, Judith; Ellis, Maggie P.; Ross, Josephine
Abstract: Alterations in one's sense of self are often considered a significant psychological symptom of dementia. However, the self is not a unified construct; it consists of a set of closely connected, yet substantive, manifestations which might not be equally impacted by dementia. Recognising the multidimensional nature of the self, the current scoping review aimed to explore the nature and scope of the evidence demonstrating change in the psychological self in people living with dementia. Adopting a cognitive psychological framework, a hundred and five (105) quantitative and qualitative studies were reviewed, and findings were organised into three main types of self-manifestations: high-order manifestations, functional aspects of the self, and foundational manifestations. Overall, the results show that although there are alterations in some of these different manifestations of the self, these do not imply a global loss of selfhood. Despite notable cognitive changes during dementia, it seems that preserved aspects of self may be enough to compensate for potential weakening of some self-processes such as autobiographical recall. Better understanding alterations in selfhood is key to addressing psychological symptoms of people living with dementia, such as feelings of disconnection and reduced agency, and may inform new pathways for dementia care interventions. Highlights: We provide a scoping review of 105 qualitative and quantitative dementia studies exploring selfhood. Although some self-alterations are present in people with dementia, these do not imply a global loss of selfhood. High-order complex manifestations of self (e.g., autobiographical memory) are more likely to be altered in dementia. Foundational aspects of the self (i.e., embodiment, agency, self-continuity) remain mostly intact in dementia. The preserved aspects of self are enough to compensate for potential weakening of some high-order self-processes.